The S-S.M.A.R.T: A New Prognostic Tool for Patients with Suspected Sepsis in the Emergency Department - Ye Jin Kim; Jong Won Kim; Kyeong Ryong Lee; Dae Young Hong; Sang O Park; Young Hwan Lee; Sin Young Kim (Emergency Medicine International)
Background. The sepsis screening tool is essential because it enables the rapid identification of high-risk patients and facilitates prompt treatment. Quick Sequential Organ Failure Assessment (qSOFA) is a widely used screening tool for sepsis. However, it has limitations in predicting patient prognosis. We developed the S-S.M.A.R.T (sepsis evaluation with shock index, mental status, age, and ROX index on triage) and aimed at evaluating it as a screening tool for patients with suspected sepsis in the emergency department. Methods. We conducted a single-center retrospective chart review of patients with suspected sepsis in the emergency department. We compared the prognosis prediction abilities of the S-S.M.A.R.T and qSOFA scores in patients with suspected sepsis. The primary outcome was 7-day mortality, and the secondary outcomes included 30-day mortality and ICU admission. The receiver operating characteristic (ROC) curve analysis and the chi-square test were used. Results. In total, 401 patients were enrolled. The mean age of the patients was 72.2 ± 15.6 years, and 213 (53.1%) of them were female. The S-S.M.A.R.T had superior predictive ability for prognosis of patients with suspected sepsis compared to qSOFA (area under the ROC curve (AUC) of 0.789 vs. 0.699; p=0.02 for 7-day mortality, AUC of 0.786 vs. 0.681; p<0.001 for 30-day mortality, AUC 0.758 vs 0.717; p=0.05 for ICU admission). Conclusion. The S-S.M.A.R.T can be useful in predicting the prognosis of patients with suspected sepsis in the emergency department.